MXene‐Based Humidity‐Responsive Actuators: Preparation and Properties. Issue 3 (1st March 2021) - Wang, Jingfeng; Ma, Haoxiang; Liu, Yuyan; Xie, Zhimin; Fan, Zhimin
Abstract: Water is a significant and abundant resource as well as a pure natural energy source. Many researchers have been reported on humidity‐responsive actuators that mimick the humidity responsive behavior that widely exists in nature. Benefiting from advantages such as hydrophilicity, high electrical conductivity, and good dispersibility, MXenes (Ti3 C2 T x ) show promising performance when applied to humidity‐responsive actuators. This Minireview describes the preparation methods and structural characteristics of MXenes, and the mechanism of humidity‐responsive actuators. Recent important advances of MXene materials in actuators are objectively reviewed and evaluated, and existing issues are discussed. In addition, the development of these systems is outlined from the aspects of MXene preparation, structure control, design and assembly, and applications, and provides new ideas and guidance for the development of the next generation of high‐performance MXene‐based humidity‐responsive actuators. Abstract : Attractive properties : MXenes (Ti3 C2 T x ) have the advantages of high hydrophilicity and excellent electrical conductivity. This Minireview concentrates on recent progress of MXene materials in the field of humidity‐responsive actuators. The preparation methods and properties of MXenes, as well as the types of MXene‐based humidity‐responsive actuators and their mechanism are discussed.